Life-Saving Emergency Adrenalectomy in a Pheochromocytoma Crisis with Cardiogenic Shock - Thalia Bekelaar; Gervais Nougon; Marc Peters; Frederic De Roeck; Steven Haine; Dirk Ysebaert; Maarten Spinhoven; Philippe G. Jorens; Rudi De Paep; Frederik Lahaye (Case Reports in Cardiology)
Cardiogenic shock during a pheochromocytoma crisis is a life-threatening disorder. This case report illustrates a 49-year-old male with profound cardiogenic shock, extreme hemodynamic instability (systolic blood pressure ranging from 45 up to 290 mmHg in a cyclic pattern), and progressive multiple organ failure in the presence of a unilateral adrenal mass. Emergency adrenalectomy led to rapid hemodynamic stabilization. Histological investigation confirmed the diagnosis of pheochromocytoma. This case indicates that emergency adrenalectomy, although usually not considered first choice, is a valid option in cardiogenic shock and extremely fluctuating hemodynamics due to a pheochromcytoma-induced catecholamine storm.